Modelling Queuing system in Healthcare centres. A case study of the dental department of the Essikado Hospital, Sekondi - Quarm, Rebecca Nduba (2016)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fufillment of the requirement for the degree of Master of Philosophy (Applied Mathematics),